2003
DOI: 10.1159/000071145
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy with Irinotecan and Ifosfamide as Second-Line Treatment of Refractory or Sensitive Relapsed Small Cell Lung Cancer: A Phase II Study

Abstract: This phase II study was conducted to investigate the efficacy and safety of irinotecan (CPT-11) and ifosfamide as second-line chemotherapy for relapsed small cell lung cancer (SCLC). Eligibility criteria included histologically or cytologically confirmed SCLC, prior chemotherapy including platinum + etoposide, and measurable or evaluable disease. CPT-11 (80 mg/m2) was administered intravenously on days 1, 8 and 15, while ifosfamide (1.5 g/m2) was given on days 1 through 3 every 4 weeks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, in spite of its successful anticancer action, the increased toxicity presented in healthy tissues and particularly in the renal and the bladder epithelium, led to its restricted usage and administration. This pressing issue was overcome with the development of mesna acting in an antioxidant fashion, was proven to successfully protect from the running risk of emergence of hemorrhagic cystitis as well as from other side effects of IFO (Anderson 2010;Ichiki et al 2003;Olver et al 2005). IFO is a well known and widely applied anticancer substance but it also has cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of its successful anticancer action, the increased toxicity presented in healthy tissues and particularly in the renal and the bladder epithelium, led to its restricted usage and administration. This pressing issue was overcome with the development of mesna acting in an antioxidant fashion, was proven to successfully protect from the running risk of emergence of hemorrhagic cystitis as well as from other side effects of IFO (Anderson 2010;Ichiki et al 2003;Olver et al 2005). IFO is a well known and widely applied anticancer substance but it also has cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies suggest great inter-patient variation in the pharmacokinetics [8] . On a 5-day infusional schedule, Cerny et al [8] reported that the optimal dose in pretreated patients was 12-14 g/m 2 , and further dose escalation did not add therapeutic benefi t but increased toxicity. However, high doses (often defi ned as over 10 mg/m 2 ) may circumvent the resistance to standard doses [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Ifosfamide, an analogue of cyclophosphamide, is an alkylating agent currently in use for the treatment of a variety of tumours including germ cell tumors, lung cancer and sarcomas [1][2][3] . It is a prodrug which is initially metabolized by P450 to therapeutically active and potentially toxic metabolites [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic activity of CPT-11 has been reported in several malignant tumors, including breast, lung, ovarian, and colon cancer (9)(10)(11)(12)(13)(14)(15)(16). CPT-11 serving as a DNA topoisomerase I inhibitor, combined with 5-fluorouracil (5-FU) and leucovorin has been accepted as a first-line treatment for patients with advanced CRC.…”
Section: Introductionmentioning
confidence: 99%